Consensus for heterogenous multi-agent systems with second-order linear and nonlinear dynamics - Shi, Y.; Yin, YanYan; Liu, C.; Liu, C.; Liu, F. (2018)
© 2018 IEEE. In this paper, we investigate the consensus for heterogeneous multi-agent systems. The systems are composed of second-order linear and nonlinear agents with different nonlinear terms, which makes systems more general. A valid control law for each agent is given based on the communication with their neighbors. By employing LaSalle's invariance principle and Lyapunov stability theory, sufficient condition is established to achieve the consensus under the undirected connected topologies. Finally, we give a simulation example to illustrate the validity of the theoretical method.